2008
DOI: 10.1590/s1020-49892008000500006
|View full text |Cite
|
Sign up to set email alerts
|

HIV risk behaviors of Latin American and Caribbean men who have sex with men in Miami, Florida, USA

Abstract: Many MSM born in LAC countries engage in HIV-related risk behaviors in the AIDS epicenter of Miami-Dade County, Florida. Culturally appropriate interventions should address these risk behaviors in this underserved population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
2
28
0
3
Order By: Relevance
“…Of those who reported UAI in past 30 days, 67% had engaged in UAI with a primary partner, whereas 44% had engaged in UAI with a nonprimary partner (Diaz, Stall, Hoff, Daigle, & Coates, 1996). A third study reported that factors associated with UAI among Hispanic MSM included a diagnosis of HIV infection, drug abuse, a greater number of sexual partners, psychosocial distress, and higher levels of acculturation (Akin, Fernandez, Bowen, & Warren, 2008).…”
Section: Condom Usagementioning
confidence: 99%
“…Of those who reported UAI in past 30 days, 67% had engaged in UAI with a primary partner, whereas 44% had engaged in UAI with a nonprimary partner (Diaz, Stall, Hoff, Daigle, & Coates, 1996). A third study reported that factors associated with UAI among Hispanic MSM included a diagnosis of HIV infection, drug abuse, a greater number of sexual partners, psychosocial distress, and higher levels of acculturation (Akin, Fernandez, Bowen, & Warren, 2008).…”
Section: Condom Usagementioning
confidence: 99%
“…Two particular SRB have been strongly associated with HIV in the general population: multiple sexual partners (12) and inadequate condom use (1). Such SRB have, however, rarely been analyzed together (13) despite recommendations to consider them combined in HIV control (14).…”
Section: Introductionmentioning
confidence: 99%
“…Although urban structure is cited as important, the differences in attitudes and sexuality-grounded roles amongst MSM even between two westernised nations must also be considered as a crucial aspect of intervention planning. Akin et al (2008) found that the sexual behaviour of Latino/Hispanic MSM in Florida was conducive to high rates of HIV transmission including psychological distress, recreational drug use, and issues around cultural and political integration. Although these factors are by no means exclusive to Latino/Hispanic MSM, or the behaviourally bisexual population, the disproportionately high HIV incidence amongst African American MSM, another minority population grouping, is not positively attributed to sexual behaviour (Malebranche 2003), thereby counteracting the popular belief that a health promotion intervention can target BME MSM as a singular group.…”
Section: The State Of Playmentioning
confidence: 99%
“…The different behavioural attitudes and risk awareness highlighted across studies such as the Akin (2008) Latino/Hispanic and Malebranche (2003) African American papers are not reflected in the HIV testing literature review. Virtually all groups analysed consistently report a lack of knowledge around testing procedures, fear of an HIV positive test result and a misperception of personal risk as the key barriers to HIV testing.…”
Section: The State Of Playmentioning
confidence: 99%